Biopulping Rami Menggunakan Jamur Pelapuk Putih - Hendro Risdianto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Ramie is a fast growing species and contains long fiber that suitable for pulpmaking. The objective of this study was to investigate the white rot fungi that can be used as a biological agent on biopulping process. A four species white rot fungi namely Phanerochaete chrysosporium, Marasmius sp., Trametes hirsuta and Trametes versicolor have been used for the pretreatment on biopulping. Each fungus was grown on ramie fiber at room temperature (±28°C) for 7 days. Lignin, cellulose and hemicellulose were observed to study the efficacy of each fungus. The result showed that Marasmius sp. could remove lignin at highest level (40.7%) than others and produced laccase at highest activity of 163,82 U/L. Cellulose and hemicellulose were insignificantly removed by fungi. At the pulping process, Kappa number of treated ramie by Marasmius sp. was lower than untreated.